Questioning Excellence in Higher Education Policies, Experiences and Challenges in National and Comparative Perspective - Rostan, Michele; Vaira, Massimiliano; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Excellence in higher education is as old as university, but nowadays the concept is widely emphasized and its meaning has been redefined on the basis of different values and goals, especially those related to market. Excellence has become the meter on which institutions are assessed and public funding allocated, the tool by which worldwide comparisons and rankings of institutions are built, and a marketable brand used by higher education institutions to present themselves. This book offers an international and comparative view on excellence in higher education, ranging from policies to practices, mainly based on research results and empirical evidence, aiming at questioning the concept and its uses which are not only social constructions but also political ones. Far from being a neutral or technical concept, excellence is heavily infused with values which must be traced, analysed and made critical to understand its impacts, backlashes and unintended outcomes on higher education systems, institutions, academics and students. The book is addressed to an international audience and in particular to higher education scholars and professionals. Those who are involved in higher education assessment, members of professional bodies and organizations in the higher education field, students in education, but also policy makers and the public opinion at large will profit from the works of a selected group of scholars coming from a variety of countries. A sense of disquietude seems ever present when discussing new digital practices. The transformations incurred through these can be profound, troublesome in nature and far-reaching. Moral panics remain readily available.
Keywords: Education; Educational tests and measurements; Education; Assessment, Testing and Evaluation